Forensic Insight: Unraveling Criminal Detection through Advanced Face Recognition and Machine Learning Techniques (International Journal of Food and Nutritional Sciences, 2022)
Criminal records contain crucialpersonal information along with photographs,often serving as vital tools for identificationpurposes.